Changes in leisure physical activity, commuting and television watching in men and women users of the Brazilian National Health System in a middle-sized city: 18-months of follow-up - Orbolato, Rafael [UNESP]; Fernandes, Rômulo Araújo [UNESP]; Turi, Bruna Camilo [UNESP]; Castanho-araujo, Monique Yndawe [UNESP]; Bortolatto, Carolina Rodrigues [UNESP]; Koyama, Kelly Akemi Kikuti [UNESP]; Morais, Luana Carolina De [UNESP]; Codogno, Jamile Sanches [UNESP] (Universidade Federal de Santa Catarina, 2018)
Given the importance of physical activity for health promotion and for the prevention of chronic non-communicable diseases, the Unified Health System (SUS) has changed its strategy of action in the last decades, trying to adopt preventive activities, seeking better quality of life of the Brazilian population and reduce costs with treatment of diseases. The aim of this study was to investigate changes in physical activity and sedentary behavior patterns in users of the Brazilian National Unified Health System during 18 months and the impact of sex and time on such variables. One hundred and ninety-eight participants (58 men and 140 women) were evaluated. Physical activity level was assessed using the Baecke questionnaire. Men had higher scores in all physical activity variables compared to women: walking (p-value= 0.013), cycling (p-value= 0.001) and commuting (p-value= 0.007), but not for TV watching (p-value= 0.362). After 18 months, in the overall sample, walking score increased 25.9% (95%CI= 10.6 to 41.1), but not cycling (1.5% [95%CI= -2.7 to 5.7]), commuting (14.4% [95%CI= -0.4 to 29.3]) and TV watching (1.6% [95%CI= -5.7 to 9.1]). Men were usually more active than women in active behaviors, but not in TV watching. However, differences over time were similar between sexes.

Dada a importância da atividade física para promoção da saúde, assim como para a prevenção de doenças crônicas não transmissíveis, o Sistema Único de Saúde (SUS) mudou a estratégia de atuação nas últimas décadas, procurando adotar atividades preventivas, buscando melhorar a qualidade de vida da população brasileira e diminuir gastos com tratamento de doenças. Objetivou-se investigar as mudanças na prática de atividade física e tempo de televisão em usuários do SUS durante um período de 18 meses e o impacto do sexo e tempo nessas variáveis. Foram avaliados 198 participantes (58 homens e 140 mulheres). Nível de atividade física foi mensurado através do questionário de Baecke. Homens apresentaram maiores escores em todas as variáveis de atividade física: caminhada (p-valor 0,013), ciclismo (p-valor 0,001) e locomoção (p-valor 0,007) do que mulheres, mas não para assistir televisão (p-valor= 0,362). Após 18 meses, em toda a amostra, o escore de caminhada aumentou 25,9% (IC95%= 10,6 - 41,1), mas não ciclismo (1,5% [95%CI= -2,7 – 5,7]), locomoção (14,4% [95%CI= -0,4 – 29,3]) e televisão (1,6% [95%CI= -5,7 – 9,1]). Entre usuários do SUS, homens foram usualmente mais ativos que mulheres em comportamentos ativos, mas não ao assistir televisão. Porém, diferenças ao longo do tempo foram similares entre os sexos.
Mudanças na atividade física de lazer, locomoção e tempo de televisão entre homens e mulheres usuários do Sistema Único de Saúde em uma cidade de médio porte: seguimento de 18 meses
Keywords: Chronic disease; Commuting; Epidemiology; Motor activity; Unified health systemPalavras-chave; Atividade motora; Doença crônica; Epidemiologia; Locomoção; Sistema único de saúde